Peran Serta Orang Tua Terhadap Prestasi Belajar Siswa di SMP Negeri 6 Palu Sulawesi Selatan (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to determine the role of parents on student achievement in the field of mathematics in Class VII SMP Negeri 6 Palu, South Sulawesi. This type of research is descriptive with a quantitative approach that aims to provide a systematic picture of the ongoing situation in the object of research, namely about the role of parents on student learning achievement in the field of mathematics in Class VII SMP Negeri 6 Palu, South Sulawesi. The sample of this study was 98 people. Based on data analysis, the results can be concluded that there is no relationship between the role of parents and student achievement in mathematics.